Reliability and validity of a Thai version of Assessment of Chronic Illness Care (ACIC) - Patama Gomutbutra (2018)
Background: The Assessment Chronic Illness Care (ACIC), developed in the United States, is a quality-improvement tool used to help organization evaluate the strengths and weaknesses of their delivery of care for chronic illness in six areas, community linkages, self-management support, decision support, delivery system design, information systems, and organization of care. These areas of care are influenced by the Chronic Care Model. The questionnaire scale ranges from 0 to 11. Objective: Translate in Thai language and validate the ACIC as a practical tool to measure the quality of chronic illness care in Thailand. Material and Method: In a cross-sectional study, the content validity was examined by public health experts. The original ACIC was translated into Thai with permission from The MacColl Institute for Healthcare Innovation at Group Health's Center for Health Studies. The translation process followed the World Health Organization (WHO) process of translation and adaptation of instruments, including forward translation, expert panel and synthesis of the translation, back translation, pre-testing, and cognitive interviewing. The pre-testing was done by distributing the questionnaire to a sample of 12 organizations with cognitive interviewing, followed by revision and finalization of the questionnaire. The reliability and validity of the translated version was then examined by distributing the questionnaire to 172 organizations (84 district hospitals and 88 community health center primary care units within the upper northern part of Thailand) focusing on care of cerebrovascular disease. Results: The response rate was approximately 70% or 120 organizations. The results from these organizations' self-assessment showed that the Thai version of ACIC achieved good levels of reliability and validity, with the range of Cronbach's alpha coefficients being 0.846 to 0.972 in each aspect of ACIC. However, ACIC inablility to detect statistical significant difference in score for each dimension though the self-management support and decision support are the two relatively low score rating. Conclusion: The Thai translation of the ACIC can be used as an organization self-assessment instrument to evaluate the quality of chronic care in Thailand. Further explanatory research of association between ACIC assessment and organization change as well as clinical outcomes is needed.